Medical and healthcare textiles - Anand, Subhash (Woodhead publishing in textiles ;, 2010)
Medical textiles remain one of the most dynamic areas of research in textiles. Medical and healthcare textiles is the fourth in a series of conferences held at the University of Bolton. Like its predecessors, it has attracted papers from some of the leading international centres of expertise in the field. Contributors cover a range of topics including emerging textile-based biomaterials, hygienic textiles, the use of textiles in infection control and as barrier materials, bandaging and pressure garments for managing chronic infections such as ulcers, the role of textiles in the management of burns and wounds, textile-based implantable devices such as tissue scaffolds and sutures, and intelligent textiles. Provides a comprehensive overview of medical textiles from the risk of infection control and barrier materials through to directives, regulations and standards shaping the medical device industryExplores developments in healthcare and hygiene products, including odor and pH control as well as protective and disposable fabricsReviews development in the area of implantable materials featuring vascular grafts, knee implants and scaffolds.